(untitled) (Baghdad Science Journal, 2025)
This study was carried out for direct detection of typhi and some of its multidrug resistance genes(tem,capt,gyrA&sul2)which encode for resistance to (Ampicillin, Chloramphenicol,Ciprofioxacin,Co-trimoxazole)by using Polymerase Chain Reaction technique .(71)blood samples for people suffering from typhoid fever symptoms depending on the clinical examination and (25)for control were collected. The results investigation for flic gene which encode for flagellin protein indicated that only (19)with percentage of (26,76%)gave appositive results while all control had a negative ones. Investigation for antibiotic resistance drug in samples which show positive results for flic gene showed that there is a multidrug for all antibiotics with (94.73%) in patients